IMPLEMENTING ECONOMIC ORDER INTERVAL FOR MULTIPLE ITEMS TO REDUCE TOTAL INVENTORY COST - Maukar, Anastasia L.; Ong, Johan Oscar; Christananta, Yoshua (Industrial and Systems Engineering Assessment Journal (INASEA), 2013)
Nowadays inventory management has become a major concern for company because it can bringÂ value added. Inventory management focuses on maintaining and managing the inventory level in order toÂ fulfill the customerâs demand with the lowest cost. In retailing and wholesaling, multiple items from the sameÂ supplier are jointly ordered. It means that the order interval of each item must be the same. However, thereÂ are several manufacturing companies that have not achieved the optimum solution in inventory managementÂ for multiple items. It leads them to increase the total inventory cost which are most caused by improper orderÂ interval. Thus, appropriate inventory management may reduce the total inventory cost. This research tried toÂ identify this problem. The first step that should be done was identifying the problems, scopes, and objectivesÂ of the research aimed to minimize the inventory control management. After that we collected data andÂ analyzed the supported data in inventory management using the total inventory cost analysis as a parameterÂ in comparing the actual system and the proposal system. This research also implemented forecastingÂ methodology to predict the future demand. In the final section, we implemented the economic order intervalÂ in order process for determining the optimum order interval. The result showed that the proposal system canÂ reduce the total inventory cost over 21% from the current condition.